Utility of Bruch membrane opening-based optic nerve head parameters in myopic subjects. Issue 1 (January 2018) - Sastre-Ibañez, Marina; Martinez-de-la-Casa, Jose M.; Rebolleda, Gema; Cifuentes-Canorea, Pilar; Nieves-Moreno, Maria; Morales-Fernandez, Laura; Saenz-Frances, Federico; Garcia-Feijoo, Julian
Purpose: To evaluate whether the new rim analysis software with spectral-domain optical coherence tomography (SD-OCT) shows advantages over the retinal nerve fiber layer (RNFL) thickness in patients with moderate myopia. Methods: In this prospective cross-sectional study, we studied 65 healthy subjects, 37 with spherical refractive errors in the range of -3 to -6 D (moderate, G1) and 28 with less than -3 D (low/non-myopic, G0). All patients were examined with Heidelberg Spectralis SD-OCT, including Glaucoma Premium Module Edition (GPME) software. With GPME, we analyzed the neuroretinal rim (Bruch membrane opening-minimum rim width [BMO-MRW]) and RNFL. Results: The average age of subjects was 30.2 ± 9.3 years for G0 and 29.9 ± 7.1 years for G1 (p = 0.903). Mean sphere was −0.5 ± 0.3 D (-1.25 to 0 D) G0 and -3.9 ± 0.3 D (-6.00 to -3 D) G1 (p<0.001). The RNFL thickness comparison between G0 and G1 showed a significantly lower thickness in G1 (p = 0.018). The BMO-MRW measurements were similar in both groups (p = 0.331). With the BMO-MRW examination, the number of sectors classified as pathologic per subject in G1 were significantly lower compared to RNFL analysis (p = 0.023). Conclusions: Ring analysis based on BMO-MRW measurements shows a lower rate of false-positives compared to RNFL thickness when studying healthy moderate myopic eyes and it would be advisable to take this into consideration when analyzing these patients.